Influence of organic solvents and acids on hydration properties of chitosan - Filatova, K.O.; Krupska, T.V.; Turov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The states of water and an aqueous solution of trifluoroacetic acid in a swollen chitosan and chitosan filled with nanosilica A-300 by low-temperature 1H NMR spectroscopy are studied. It is shown that the main part of water in the polymer matrix is included in the domains with R > 10 nm. Introduction of nanosilica into the polymer matrix reduces the binding energy by almost 30 % through the formation of bonds between chitosan and silica (water displacement in the gaps between the biopolymer and SiO2). In the presence of a strong acid (TFA), polyassociations of water with varying solubility relative to acids within the polymeric matrix of pure chitosan and chitosan filled with SiO2 are present, while a large part of water refers to the domains, which dissolve the acid poorly.